Outcomes of cardiopulmonary resuscitation performed in Emergency Department, Hospital Universiti Sains Malaysia. - Chew, K S; Idzwan, Z M; Hisamuddin, N A R; Kamaruddin, J; Wan Aasim, W A (2008)
Despite the progresses made in the science of cardiopulmonary resuscitation, there is lack of published works on this area in the Malaysian context. This survey was done to look at the outcomes of all cardiopulmonary resuscitation performed in Emergency Department (ED), Hospital Universiti Sains Malaysia (HUSM). This is a one year cross-sectional study from March 2005-March 2006. All adult cardiac arrest cases with CPR performed in ED, HUSM were included in the survey. The end points are return of spontaneous circulation (ROSC) and survival to ward admission. Out of the total 63 cases of cardiac arrest with CPR performed, only 19 cases (30.2%) had ROSC after CPR performed on them. Eventually only six patients (9.5%) had survival to ward admission. Patients with shockable intial arrest rhythm has a significantly higher chance to achieve ROSC (60.0%) compared to non-shockable rhythms (24.5%) (p = 0.025). However, there was no different in survival to ward admission between shockable and non shockable rhythms groups. The survival after cardiac arrest is still dismally poor. Perhaps we should be more selective in initiating CPR especially for out of hospital cardiac arrest.